Relasi Agama dan Negara: Harta dan Kepemilikan dalam Perspektif Islam - Akbar, Aziz; Sulastri, Sulastri (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2024)
Abstract This article delves into the concept of wealth (harta) in Islam, emphasizing its multidimensional nature beyond mere material possession. Through etymological analysis and theological insights, it elucidates wealth as encompassing ethical, social, and spiritual dimensions. The discussion navigates through various classifications of wealth, including tangible and intangible assets, and delineates Islam's stance on ownership, emphasizing responsible stewardship guided by religious principles. Furthermore, the article explores Islam's perspective on the role of wealth within society, positioning it among the five essential human needs according to Islamic jurisprudence. It underscores the imperative for wealth management grounded in moral values and societal welfare, emphasizing the importance of equitable distribution and communal prosperity. Ultimately, the article underscores Islam's call for conscientious utilization of wealth, not only as an individual prerogative but also as a collective responsibility towards fostering social justice and communal well-being.